Diversity of Cultivable Protease-Producing Bacteria in Laizhou Bay Sediments, Bohai Sea, China - Li, Yan; Wu, Chaoya; Zhou, Mingyang; Wang, En Tao; Zhang, Zhenpeng; Liu, Wei; Ning, Jicai; Xie, Zhihong (Frontiers in Microbiology, 2017)
Protease-producing bacteria are widespread in ocean sediments and play important roles in degrading sedimentary nitrogenous organic materials. However the diversity of the bacteria and the proteases involved in such processes remain largely unknown especially for communities in enclosed sea bays. Here, we investigated the diversity of the extracellular protease-producing bacteria and their protease types in Laizhou Bay. A total of 121 bacterial isolates were obtained from sediment samples in 7 sites and their protease types were characterized. The abundance of cultivable protease-producing bacteria was about 104 CFU g-1 of sediment. Phylogenetic analysis based on 16S rRNA gene sequences suggest that the isolates belonged to 17 genera from 4 phyla including Firmicutes, Actinobacteria, Proteobacteria and Bacteroidetes, and mainly dominated by the genera Pseudoalteromonas (40.5%), Bacillus (36.3%) and Photobacterium (5.8%). The diversity and community structure varied among different sampling sites but no significant correlation was observed with soil sediment’s characteristics. Enzyme activity and inhibition tests further revealed that all isolates secreted proteases that were inhibited by serine and/or metalloprotease inhibitors, and a smaller proportion was inhibited by inhibitors of cysteine and/or aspartic proteases. Furthermore, all isolates effectively degraded casein and/or gelatin with only a few that could hydrolyze elastin, suggesting that the bacteria were producing different kinds of serine proteases or metalloproteases. This study provided novel insights on the community structure of cultivable protease-producing bacteria near the Yellow River estuary of an enclosed sea bay.